Microbial Population and Nutrient Content of a Biofertilizer Containing Azotobacter sp. and Pseudomonas fluorescens with Different Carrier Materials After Storage - Elita, Nelson; Erlinda, Rita; Yefriwati, Yefriwati; Yanti, Rinda; Sari, Deliana Andam; Illahi, Ayu Kurnia; Maulina, Fri; Hasan, Nor’ Aishah (Green Engineering Society, 2025)
Biofertilizers contain N-fixing and P-solubilizing bacteria. The microbial population is dynamic and influenced by nutrient availability and storage temperature. Maintaining microbial populations requires appropriate carrier media to maximize microbial viability. The aim of the research is to determine the appropriate carrier material for the biofertilizer after storage based on the nutrient content and microbial population. The experiment utilized a completely randomized design with seven treatments and four replications, resulting in 28 experimental units. The treatments were as follows: B0 = Compost, B1 = Compost + Bacteria (Azotobacter and Pseudomonas fluorescens), B2 = Compost + Bacteria (Azotobacter + P. fluorescens) + Molasses, B3 = Compost + bacteria (Azotobacter + P. fluorescens) + CMC, B4 = Compost + bacteria (Azotobacter + P. fluorescens) + Arginine, B5 = Compost + bacteria (Azotobacter + P. fluorescens) + Sugar + CMC, and B6 = Compost + bacteria (Azotobacter + P. fluorescens) + Molasses + Arginine. The study results showed that the highest bacterial colonies were observed seven days after storage in treatment B2, reaching 156.33 CPU. The highest bacterial population growth in the first month was recorded in treatment B5; however, in months 2, 3, 4, and 5, treatment B2 exhibited the highest bacterial colony population. The pH remained more stable in treatments B2, B4, and B6. The highest nutrient content, including pH, N, P, K, and C/N ratio, was recorded in treatment B2, respectively, with values of 6.67, 2.49%, 2.04%, 1.77%, and 20.01. Findings in this study suggested the potential biofertilizer can be applied in the field to reduce dependence on chemical fertilizers to support sustainable agriculture.